The Effect of Job Satisfaction and Organizational Climate Factors on Employee Performance at the Education Office of Bone Regency - Kasma, Kasmawati; Rianti, Marlia; Badaruddin (Cendekiawan Indonesia Timur, 2022)
This study aims to determine the effect of job satisfaction and organizational climate on performance. This research was conducted at the Bone Regency Education Office for three months, using a survey research method from May to July 2021. The population in this study were all employees at the Education Office of Bone Regency, as many as 135 people. The results showed that 1) job satisfaction consisting of salary, work itself, promotion, supervision, and organizational climate consisting of responsibility, identity, warmth, support, conflict simultaneously had a positive and significant effect on employee performance; 2) salary is a variable of job satisfaction factor that has a positive and significant and most dominant influence on employee performance; 3) warmth is a variable of organizational climate factor that has a positive and significant; 4) successive variables based on their influence on employee performance are salary, warmth, promotion, job description, identity, conflict, responsibility, support, and supervision.